2009
DOI: 10.3989/scimar.2009.73n3431
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns in the population structure of the whelk <em>Stramonita haemastoma</em> (Linnaeus, 1766) (Gastropoda: Muricidae) in the Canarian Archipelago (eastern Atlantic)

Abstract: SummaRy: The goal of this study was to determine the consistency of the vertical distribution patterns of the predatory whelk, Stramonita haemastoma, in the rocky intertidal zone of the canarian archipelago (eastern atlantic) across a hierarchy of five orders of magnitude of horizontal spatial variability (from tens of m to hundreds of km). in general, this species showed a consistent vertical zonation pattern across islands, with the majority of the specimens (74.65%) found in the mid intertidal zone. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
2
6
0
7
Order By: Relevance
“…Stramonita haemastoma preferred stretches closer to the lower shore, as also observed in previous studies (Rilov et al, 2001;Calil, 2007). This strategy of inhabiting areas with longer submersion times probably minimises the effects of thermal variation and desiccation.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Stramonita haemastoma preferred stretches closer to the lower shore, as also observed in previous studies (Rilov et al, 2001;Calil, 2007). This strategy of inhabiting areas with longer submersion times probably minimises the effects of thermal variation and desiccation.…”
Section: Discussionsupporting
confidence: 72%
“…The presence of holes and crevices, especially in N1, presumably confers protection from predators. Rilov et al (2001) also observed higher abundances of S. haemastoma in the lower intertidal zone on the coast of Israel, and attributed this to greater availability of food and shelter. In this study, protection against the physiological stress caused by temperature variations explains why there were fewer individuals of S. haemastoma at the upper level of both sampling sites, where the temperature varies more than at the lower level.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This predatory whelk with planktonic larvae (Scheltema 1971) preferentially inhabits rocky shores (Rilov et al 2001, Ramirez et al 2009), where it preys on animals such as oysters, barnacles, gastropods, and bivalves (Rilov et al 2004, Lopez et al 2010). …”
Section: Abstract: Evolution On Islands · Predatory Impact · Island mentioning
confidence: 99%